Model Misspecification as the Causes of Flypaper Effect - Siniša Mali (Proceedings, 2023)
The aim of this paper is to investigate the relationship between the Fly-paper effect (FPE) and possible errors in the specification of econometric models used in the empirical analysis of FPE. Using desk research method to gathering and analyzing scientific papers considering different aspects of misspecification problem, it was executed classification of papers in three groups depending on the type of errors in the model specification: incorrect functional form, incorrect choice of explanatory variables and incorrect statements about stochastic error of model. Research results showed that the wrong specification of the model affects the presence or absence of FPE) and the size of the FPE. The originality of this paper is reflected in the original classification of scientific papers devoted to the problem of misspecification of regression models used for econometric modeling of FPE. The contribution of this work is reflected in the identification of possible errors in the specification of the model for the empirical analysis of FPE and their implications on the properties of the parameter estimates of the used model.